Linking crop productivity, market participation and technology use among smallholder farmers: Evidence from Uganda - Mpuuga, Dablin; Nakijoba, Sawuya; Ogwang, Ambrose; Boughton, Duncan; Benfica, Rui (Michigan State University Press, 2023)
In this paper, we establish the link between crop productivity, crop market participation and agricultural technology use among smallholder farmers. We take advantage of the latest four waves of the Uganda National Panel Survey – 2013/14, 2015/16, 2018/19, and 2019/20. First, we test for complementarity of agricultural technology use among smallholder farmers, and we do not find evidence for the combined effect of organic and inorganic fertilizers as well as pesticides and organic fertilizers on crop yields, which implies that there is lack of complementarity. More precisely, smallholder farmers mostly use these agricultural technologies in isolation. However, we find strong individual effect of organic fertilizers on cassava, beans, and coffee yields. Second, we use a two-step factor analysis to construct four technology sub-indexes for improved seeds, pesticides, organic, and inorganic fertilizers in the first step and the overall agricultural technology index in the second step. We run crop-specific models and the results re-affirm a positive effect of agricultural technology use on both cassava and coffee yields. Third, when we attempt to measure crop productivity as farm productivity, we find that a unit increase in inorganic fertilizers used increases farm crop productivity by 69%. We do not see this strong effect of inorganic fertilizers on our partial measure of crop productivity – crop yields – which implies that the way we measure crop productivity matters. We therefore conclude that of the four agricultural technologies, inorganic fertilizers have the strongest individual effect on farm productivity of smallholder farmers. Fourth, we employ the Heckman twostep technique to correct the selection bias in crop market participation outcomes. We do not find strong evidence of the effect of agricultural technology use on crop market participation, but we find that it is rather crop yields that are most critical for market participation. Therefore, a farmer’s cropproductivity is arguably the most critical facilitator or inhibitor of their market participation. More precisely, to boost crop market participation among smallholder farmers, increasing their productivity is a necessary condition.